2019
DOI: 10.5194/nhess-19-973-2019
|View full text |Cite
|
Sign up to set email alerts
|

Water-level attenuation in global-scale assessments of exposure to coastal flooding: a sensitivity analysis

Abstract: This study explores the uncertainty introduced in global assessments of coastal flood exposure and risk when not accounting for water-level attenuation due to landsurface characteristics. We implement a range of plausible water-level attenuation values for characteristic land-cover classes in the flood module of the Dynamic and Integrated Vulnerability Assessment (DIVA) modelling framework and assess the sensitivity of flood exposure and flood risk indicators to differences in attenuation rates. Results show a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 56 publications
0
50
0
Order By: Relevance
“…To calculate overland inundation from near-shore tide and surge levels we used a GIS-based inundation routine, similar to Vafeidis et al (2019). Extreme sea levels from the nearest GTSR location are projected at the coastline.…”
Section: Flood Hazardmentioning
confidence: 99%
“…To calculate overland inundation from near-shore tide and surge levels we used a GIS-based inundation routine, similar to Vafeidis et al (2019). Extreme sea levels from the nearest GTSR location are projected at the coastline.…”
Section: Flood Hazardmentioning
confidence: 99%
“…Beck et al (2018) estimate the global flood protection savings that can be provided by coral reefs. Vafeidis et al (2019) investigate the uncertainty introduced to global coastal risk modelling by the flood attenuation land inwards. They show that the uncertainties in attenuation are similar in size to the uncertainties in sea level rise, suggesting this is an important future research direction.…”
Section: Coastal Floodsmentioning
confidence: 99%
“…For coastal flooding, the fully hydrodynamic model GTSM is now being used to simulate water levels due to surge and tide up to the coastline, but then simple planar models are used to translate these water levels into inundation maps on land. Vafeidis et al (2019) have shown the importance of accounting for hydrodynamic processes by developing an approach to assess the impacts of water-level attenuation due to different land cover on flood hazard. This approach can be used as a first step towards improving global coastal flood risk assessment.…”
Section: Hazardmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of the assessment is applying a bathtub model that assumes all coastal land below a given water level and hydrologically connected to the ocean or behind protection structures such as levees, as potentially exposed directly or indirectly to flooding from extreme coastal water levels (including groundwater). The bathtub approach tends to overestimate coastal flooding extents at local-scales when caused by episodic events and to a larger extent along mildly sloped terrains [36,37]. In New Zealand, these terrains are representative of most major urban areas with >30,000 population.…”
Section: Limitationsmentioning
confidence: 99%